Diabetes: how to manage overweight and obesity in type 2 diabetes mellitus - Megan Wesling; Jennifer J D'Souza (BioExcel Publishing Ltd, 2022)
The prevalence of obesity worldwide continues to increase substantially. Obesity is a chronic disease that can lead to other health conditions, including type 2 diabetes mellitus (T2DM). A variety of treatment options are available to treat T2DM. With its prevalence increasing, it is essential that healthcare professionals assess how their patients' current diabetes treatment is being managed to avoid further weight gain in those with overweight or obesity.